If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + -5 = 9 + 13x Reorder the terms: -5 + 20x = 9 + 13x Solving -5 + 20x = 9 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -5 + 20x + -13x = 9 + 13x + -13x Combine like terms: 20x + -13x = 7x -5 + 7x = 9 + 13x + -13x Combine like terms: 13x + -13x = 0 -5 + 7x = 9 + 0 -5 + 7x = 9 Add '5' to each side of the equation. -5 + 5 + 7x = 9 + 5 Combine like terms: -5 + 5 = 0 0 + 7x = 9 + 5 7x = 9 + 5 Combine like terms: 9 + 5 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| 22x+2=19x-4 | | -(-49-2b)-(3b+6)= | | 22x+2+19x-4=90 | | 16x-12=17x | | 18=4y | | 5+6q=9+5q | | -11(4k+6)=198 | | .66x+92=-31 | | 8x-9=7x-7 | | -64x^2+120x-42=0 | | 3(a+2)+4a=2(a-7) | | -4f-(-8)=4f+(-8) | | 0.4x+3=0.3x | | 5x-1.3= | | h=-4.9x^2+60x+38 | | 2x+10=x+86 | | x=2(6+2)(5-3) | | 7t+6t=13t | | 3y-15=y-15 | | n+2n+3n+(4+5)n+6(7+2n)= | | 6[5-(8x-9)]+7x=0 | | -5*x-1=-9 | | 4x=4x+134 | | 6z+6+2z-4=90 | | x*-5-1=-9 | | -4g+5=-7g-10 | | 4-9[7-(8x-8)]= | | 17-9x=80 | | h^2-h+42=0 | | u=72 | | 3x^2+7x+11=0 | | T+12=-4 |